High resolution images from low resolution video sequences - Cristina, Federico (2005)
In some cases, low resolution of those images composing a video film hinders the proper visual interpretation of its data. A typical example of this is video obtained from security cameras. There thus exists the need to count with some method allowing the processing of such information in order to obtain a better quality and a higher level of detail of those images. This gives rise to the possibility of making a more reliable interpretation of images, all of which eases the determination of, for example, some people face features or a car plate numbers. Nowadays, there exist some techniques that are related to this topic (called Image Super- Resolution techniques), though in the theoretical field in principle. Besides, there is no integral solution presented as integral product for its utilization. This paper presents the preliminary results of the Super-Resolution techniques applied to video sequences with the possibility of using quality enhancement preprocessing in each individual image.